High-resolultion reconstruction of Lena River discharge during the Late Holocene inferred from microalgae assemblages - Polyakova, Ye. I.; Klyuvitkina, T. S.; Golovnina, E. A.; Bauch, Henning; Kassens, Heidemarie (Deutsche Gesellschaft für Polarforschung; Alfred-Wegener-Institu für Polar- und Meeresforschung, 2006)
On the basis of a detailed study of the diatom and aquatic palynomorph assemblages and a detailed radiocarbon chronology of sediment cores obtained from the south-eastern inner Laptev Sea shelf adjacent to the Lena Delta the spatial and temporal variability in the Lena River discharge during the last 6 cal. ka were reconstructed. It was shown that in the area adjacent to the Lena Delta variations in surface water salinities, reconstructed using freshwater diatoms as a proxy, were mainly caused by changes in the volume of the Lena River runoff through the major riverine channels Trofimovskaya, Bykovskaya and Tumatskaya. Several paleohydrological phases are recognized: (i) establishment of modern-like conditions within the eastern Lena River Valley occurred from 6-4.2 cal. ka; (ii) Lena River outflow increased in north-eastward direction via the Trofimovskaya or Bykovskaya channels from 4.2-2.7 cal. ka, coeval with a reduction of runoff toward the north via the Tumatskaya Channel; (iii) generally stable hydrological conditions northward of the Tumatskaya Channel and variations in riverine discharge north-eastward of the Trofimovskaya and Bykovskaya channels prevail since 2.7 cal. ka. Using indicator species of dinocysts as principle marine proxy, an influence of Atlantic water to the southeast inner Laptev Sea shelf could be inferred, possibly along the Eastern Lena paleovalley, brought into this area by winddriven reversed bottom currents. Zusammenfassung: Untersuchungen von Diatomeen- und aquatischen Palynomorphen-Vergesellschaftungen wurden an Radiokohlenstoff datierten Sedimentkernen aus der inneren südöstlichen Laptevsee nahe des Lenadeltas durchgeführt. Anhand dieser Daten wurde die zeitliche und räumliche Veränderlichkeit des Flusswasserausstromes der Lena für die letzten 6 ka (Kalenderjahre) rekonstruiert. Zeitliche Veränderungen in den Häufigkeiten von Süßwasserdiatomeen sind begründet durch Wechsel in der Menge des Lenaausflusses durch die drei großen Haupkanäle im Delta: Trofimovskaja, Bykovskja, sowie ...